An Examination of Disinfection and Sterilization Practices, Attitudes, and Knowledge in Healthcare Facilities - ELSAYED, ATEF EID MADKOUR; Saud, Hani ajaab; Alhamzah, Fahad Saleh Ibrahim; Alharbi , Aqeel Ghunaim Aqeel; Awaji, Abdullah Ahmed Hussain; Alamri , Abdullah ali Abdullah; Alshehri, Abdulhadi Abdullah Ahmad (Journal of Ecohumanism, 2024)
Background: Healthcare-associated infections (HAIs) are a significant global concern, leading to increased morbidity, mortality, and healthcare costs. Effective disinfection and sterilization practices among healthcare workers (HCWs), particularly nurses, are vital for preventing HAIs. However, adherence to established protocols is inconsistent, and research examining the knowledge, attitudes, and practices of nurses in this domain is limited. Methods: This study assessed the knowledge, attitudes, and compliance with disinfection procedures among a random sample of nurses from eight public hospitals. Data were collected through structured face-to-face interviews using a validated questionnaire. Statistical analyses included multivariate logistic and linear regression to evaluate predictors of knowledge, attitudes, and compliance with disinfection practices. Results: Of the 540 nurses approached, 533 participated (response rate: 98.7%). While most nurses recognized the importance of disinfection in preventing HAIs, only 30% correctly identified urinary and respiratory tract infections as the most common HAIs. Higher education levels were significantly associated with greater knowledge and adherence to proper disinfection practices (OR = 1.68, p = 0.028). Despite positive attitudes toward disinfection protocols, adherence to correct practices varied, with only 62.6% appropriately disinfecting surgical wounds and 57.5% performing proper hand hygiene. The majority expressed a strong interest in further education on disinfection. Conclusion: This study highlights critical gaps in nurses’ knowledge and inconsistent adherence to disinfection protocols despite positive attitudes. Addressing these deficiencies through targeted education and training programs is essential to improve compliance, enhance patient safety, and reduce the incidence of HAIs.